Enhancing Thai student-teacher problem-solving skills and academic achievement through a blended problem-based learning approach in online flipped classrooms - Paitoon Pimdee; Aukkapong Sukkamart; Cherisa Nantha; Thiyaporn Kantathanawat; Punnee Leekitchwatana (My University, 2024)
The study aimed to develop a learning model that enhances Thai student-teacher problem-solving skills (PSS) and academic achievement (AA) through a blended problem-based learning (PBL) approach in online flipped classrooms. Phase 1 consisted of the design of the Flipped PARSER (problem-attempt-research-solutions-evaluation-reflect) Model (FPM) through the study of documentation and research. Phase 2 involved using nine experts to assist with the model's development and evaluation using in-depth interviews and content analysis. Phase 3 involved the application and use of the FPM by 30 student-teachers, from which their AA, PSS, and satisfaction were evaluated against the control group of 31 participants. The results from the nine experts' input on the FPM design were significant. Instructor activities included selecting content, media, materials, and their design and development. Other components included learning activities, tools, lesson delivery, and evaluation. Also, PBL methods were again confirmed as an instrumental pedagogy in teaching PSS. When combined with online learning and flipped classrooms, the study's results were higher than those using traditional classroom methods. The study contributes to the literature by determining that online teaching models effectively teach PSS and raise AA scores.
Keywords: Flipped Classroom; Blended Learning; Problem-Based Learning; Flipped learning; Innovative Teaching Methods